Les progrès en compréhension de récits chez des élèves présentant des troubles du développement intellectuel - Sylvie Cèbe; Florence Lévite (Nantes Université, 2015)
In 2005, the French government passed two laws which are going to radically change the missions assigned to the school system. The first, the law for the equality of rights and chances for disabled people, recognizes the right for every child with a handicap to be enrolled in an ordinary school. The second, the law of orientation and program for the future of schools, commits the teachers to guarantee to these pupils the mastery of the skills defined by the common base, in which the first priority is given to "the language ability" and particularly to "the capacity to read and to understand varied texts". But is it really possible to reach this goal with pupils presenting significant disorders in intellectual development? To bring an answer to this question, we led an original experiment in an inclusive classroom (CLIS) welcoming pupils, from 7 to 9 years old. It was designed to estimate the effects of the implementation of a device adapted to those pupils' particular needs and to teach them ways to understand a long text, to memorize the main events within, and to retell the story. The results allow us to argue that the proposed adaptations are relevant because they produced positive effects on these three aspects.